Estimation Error in the Correlation of Two Random Variables: A Spreadsheet-Based Exposition - Clarence C. Y. Kwan (Spreadsheets in Education, 2009)
Although the statistical term correlation is well-known across many academic disciplines, estimation error in the correlation has traditionally been considered to be a topic too difficult for students outside statistical fields. This pedagogic study presents an approach for the estimation that does not require any advanced statistical concepts. By using familiar spreadsheet functions to facilitate the required computations, it intends to make the analytical material involved accessible to more students.